Is Legal Reform the Answer to Dispute Resolution in the Construction Services Sector? A Critical Look at Law No. 2 of 2017 - Jeffry Yuliyanto Waisapi; Slamet Suhartono; Yovita Arie Mangesti; Rosalinda Elsina Latumahina; Felina C Young (Journal of Law and Legal Reform)
Disputes in the construction services sector are inevitable due to the complexity of contracts, project delays, cost overruns, and quality issues. Law No. 2 of 2017 on Construction Services seeks to reform dispute resolution mechanisms by emphasizing alternative dispute resolution (ADR), mediation, and arbitration while ensuring legal certainty and fairness. This study analyzes these reforms using a quantitative survey approach to assess their effectiveness and identify existing gaps. The Construction Services Acts of 1999 and 2017 marked significant philosophical and procedural shifts, with the latter focusing on non-litigious settlements through a win-win approach. However, challenges remain, particularly regarding the interpretation of the term "court" and the enforcement of decisions. Findings indicate that while Law No. 2 of 2017 promotes ADR mechanisms, enforcement issues, contractual inconsistencies, and power imbalances between large developers and smaller contractors hinder its effectiveness. The Act also establishes a team formed by mutual agreement to oversee construction services and mediate disputes, yet concerns persist over defects, nonconformities, weaknesses, and perceived biases in its implementation. Despite these challenges, Indonesia is progressing toward more effective construction dispute resolution. To enhance future regulatory frameworks, this study recommends stricter sanctions for violations of construction agreements and improved procedural clarity. Comparative insights from international legal frameworks suggest that Indonesia could benefit from integrating global best practices, such as adjudication boards and expedited arbitration. These findings are crucial for legal practitioners and policymakers in refining dispute resolution mechanisms and raising public awareness of regulatory gaps that hinder sustainable development.